Escape from parasitism by the invasive alien ladybird, Harmonia axyridis. Issue 4 (2nd December 2013) - Comont, Richard F.; Purse, Bethan V.; Phillips, William; Kunin, William E.; Hanson, Matthew; Lewis, Owen T.; Harrington, Richard; Shortall, Christopher R.; Rondoni, Gabriele; Roy, Helen E.; Leather, Simon R.; Sait, Steven
Abstract Alien species are often reported to perform better than functionally similar species native to the invaded range, resulting in high population densities, and a tendency to become invasive. The enemy release hypothesis (ERH) explains the success of invasive alien species (IAS) as a consequence of reduced mortality from natural enemies (predators, parasites and pathogens) compared with native species. The harlequin ladybird, Harmonia axyridis, a species alien to Britain, provides a model system for testing the ERH. Pupae of H. axyridis and the native ladybird Coccinella septempunctata were monitored for parasitism between 2008 and 2011, from populations across southern England in areas first invaded by H. axyridis between 2004 and 2009. In addition, a semi‐field experiment was established to investigate the incidence of parasitism of adult H. axyridis and C. septempunctata by Dinocampus coccinellae. Harmonia axyridis pupae were parasitised at a much lower rate than conspecifics in the native range, and both pupae and adults were parasitised at a considerably lower rate than C. septempunctata populations from the same place and time (H. axyridis: 1.67%; C. septempunctata: 18.02%) or in previous studies on Asian H. axyridis (2–7%). We found no evidence that the presence of H. axyridis affected the parasitism rate of C. septempunctata by D. coccinellae. Our results are consistent with the general prediction that the prevalence of natural enemies is lower for introduced species than for native species at early stages of invasion. This may partly explain why H. axyridis is such a successful IAS.